Psychological Analysis of Sports Consumers and Its Application in Rural Collective Economy Industry - Hao Lu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research aimed to explore the psychological analysis of sports consumers and its application in the rural collective economy industry. Select the top six cities in GDP ranking, namely (A city, B city, C city, D city, E city, F city), in each city, 4 out of 24 comprehensive operational sports and fitness service enterprises with fitness projects as their main business were selected based on consumer satisfaction, and 600 consumers' consumption behaviour was randomly selected as the research object. In terms of purchasing attitude, the most significant impact is the substantive stimulus among the stimulus factors, the correlation coefficient between the two is as high as 0.789, indicating that consumers' actual purchasing attitude is still influenced by factors such as the quality and function of sports products or the relevant services and prices provided in sports consumption venues.The product information reflected in stimulating factors and the consumer's own nature reflected in external factors are interrelated, which plays an important role in influencing consumer preferences and adjusting real consumption behaviour. The study also contributed a significant results which suggest the need for sports businesses to prioritize service-oriented offerings and invest in product quality and facilities to enhance consumer satisfaction and stimulate sports consumption.